Compound Words in Andre Aciman's Call Me by Your Name - Nirwana Nilam Sari; Putu Weddha Savitri; Ni Luh Sutjiati Beratha (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research entitled “Compound Words in André Aciman’s Call Me by Your Name” is interesting to be discussed further since compound word is one of the most productive types of word formation process in English. This research was aimed to find out the types of compound words and to analysed the meaning of the compound words in André Aciman’s novel entitled Call Me by Your Name. The data of this research were taken from the novel Call Me by Your Name written by André Aciman. The documentation method and note-taking technique was used in this research to collect the data. The qualitative method was used in this research to analyse the data that has been collected. The data that has been analysed were presented in formal and informal form. The results of this research explained that there are four types of compound words found in the novel Call Me by Your Name. There were found 198 nominal compounds, 39 verbal compounds, 14 adjectival compounds, and 6 neoclassical compounds. There were found 183 transparent meanings, and 74 opaque meanings. Therefore, there were found 257 compound words.